Revisiting Effective Communication Between Patients and Physicians: Cross-Sectional Questionnaire Study Comparing Text-Based Electronic Versus Face-to-Face Communication - Mirzaei, Tala; Kashian, Nicole (JMIR Publications, 2020)
BackgroundResearch has shown that text-based communication via telemedicine will continue to be a mode of communication that patients and physicians use in the future. However, very few studies have examined patients' perspectives regarding the increased use of text-based communication versus face-to-face (FtF) communication. ObjectiveThis study aimed to understand and compare the potential differences in patients' perceptions of communication effectiveness with their physicians through different modes of communication. MethodsWe conducted a web-based survey of 345 patients to explore the impact of different channels on effective communication and perceived health behavior and outcomes. We tested the impact of patients' perceived communication and media effectiveness on their self-efficacy, communication satisfaction, and perceived health outcomes, separately for text-based information technology (IT)-mediated communication and FtF communication. Furthermore, we conducted a group comparison to identify significant differences across these 2 groups. ResultsWe found no significant differences between patients' perceptions of effective communication using either IT-mediated communication or FtF communication with their physicians. However, we found significant differences in patients' perception of media effectiveness: patients perceived FtF communication to be a more favorable medium (P=.02). Interestingly, we found no significant difference in terms of benefits (P=.09) and success (P=.08) of IT-mediated communication versus FtF communication. ConclusionsThe results of this study imply that patients can achieve the same level of communication effectiveness with their physicians using IT-mediated communication as they would in comparable FtF interactions, but patients view FtF communication to be a more favorable medium than IT-mediated communication.